Diabetes Mellitus, Hypertension & Associated Factor’s among students of Jazan in the Kingdom of Saudi Arabia - Hobani, Yahya Hasan; Mathew, Shiju; Samsam, Hassan Ali (International Journal of Applied Sciences and Biotechnology, 2015)
Background: Health-related issues has been one of the major factor of concern for the death since the last three decades in Saudi Arabia which includes diabetes mellitus, hypertension and other associated factors are considered as major risk factors. The investigation on the prevalence of Diabetes, Hypertension and associated factors among students of Jazan, Saudi Arabia is an alarm for the hidden possible health threat among the students in the younger age. Methods: The study aimed to assess the prevalence of Diabetes, Hypertension and associated factors in fifty students of Jazan in Kingdom of Saudi Arabia. Data were collected through interview using a structured questionnaire followed by clinical examination. Clinical practice methods were followed to estimate Cholesterol, Body Mass Index (BMI), weight, Diabetes and Hypertension from the sample. Results: A high percentage of participants i.e. 70% are pre diabetes, which is partly due to a more sedentary lifestyle and smoking and weight gain. 62% of participants reported no physical exercise in daily life. Habit of smoking is present among 44% of the participants over weight and obesity showed as 24% and 16% respectively. The high blood pressure among the participants was 36% and 64% were prehypertensive. Obesity and weight assessed by using Body Mass Index. The result showed 52% among the participants were in normal weight, 24% were overweight and 16% were obese. CONCLUSION: The prevalence of Smoking, physical inactivity, obesity and cholesterol level were associated with the risk of Pre-hypertension, hypertension, pre-diabetics and diabetics. Int J Appl Sci Biotechnol, Vol 3(4): 708-713